Muscle-enriched microRNA miR-486 decreases in circulation in response to exercise in young men - Aoi, Wataru; Ichikawa, Hiroyuki; Mune, Keitaro; Tanimura, Yuko; Mizushima, Katsura; Naito, Yuji; Yoshikawa, Toshikazu (Frontiers in Physiology, 2013)
Background: MicroRNAs (miRNAs) are small non-coding RNAs involved in post-transcriptional gene regulation. miRNAs are taken in by intracellular exosomes, secreted into circulation, and taken up by other cells, where they regulate cellular functions. We hypothesized that muscle-enriched miRNAs existing in circulation mediate beneficial metabolic responses induced by exercise. To test this hypothesis, we measured changes in muscle-enriched circulating miRNAs in response to acute and chronic aerobic exercise. Methods: Eleven healthy young men (age, 21.5 ± 4.5 y; height, 168.6 ± 5.3 cm; and body weight, 62.5 ± 9.0 kg) performed a single bout of steady-state cycling exercise at 70% VO2max for 60 min (acute exercise) and cycling training 3 days per week for 4 weeks (chronic exercise). Blood samples were collected from the antecubital vein before and after acute and chronic exercise. RNA was extracted from serum, and the levels of muscle-enriched miRNAs (miR-1, miR-133a, miR-133b, miR-206, miR-208b, miR-486, and miR-499) were measured. Results: All of these miRNAs, except for miR-486, were found at too low copy numbers at baseline to be compared. miR-486 was significantly decreased by both acute (P = 0.013) and chronic exercise (P = 0.014). In addition, the change ratio of miR-486 due to acute exercise showed a significant negative correlation with VO2max for each subject (R = 0.58, P = 0.038). Conclusion: The reduction in circulating miR-486 may be associated with metabolic changes during exercise and adaptation induced by training.